2019
DOI: 10.1021/acs.jpcc.9b00124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HF Pressure on Thermal Al2O3Atomic Layer Etch Rates and Al2O3Fluorination

Abstract: Thermal Al2O3 atomic layer etching (ALE) can be accomplished using sequential fluorination and ligand-exchange reactions. HF can be employed as the fluorination reactant, and Al­(CH3)3 can be utilized as the metal precursor for ligand exchange. This study explored the effect of HF pressure on the Al2O3 etch rates and Al2O3 fluorination. Different HF pressures ranging from 0.07 to 9.0 Torr were employed for Al2O3 fluorination. Using ex situ spectroscopic ellipsometry (SE) measurements, the Al2O3 etch rates incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 48 publications
7
97
0
Order By: Relevance
“…Among these materials, AlO x has been widely applied in gate insulator layers [15,16,17,18] and has attracted extensive attention in the RRAM field owing to its wide band gap (~8.9 eV), high thermal stability with Si and Pt, high dielectric constant (~8) and large breakdown electric field [10,14,19,20,21,22] as Kim et al has reported [19,20,23,24,25,26]. In addition, the superior elasticity [27] and high toughness [28] make it possible for AlO x to be applied under various conditions including vibration and pressure environments [29,30,31]. Cano et al reported that AlO x -based dielectric layer showed superior stability under environments with hydrofluoric acid pressure [29] and Choi et al reported large-scale flexible electronics application with AlO x thin film [31], which have demonstrated that the AlO x thin film has great potential as a metal oxide layer in RRAM devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these materials, AlO x has been widely applied in gate insulator layers [15,16,17,18] and has attracted extensive attention in the RRAM field owing to its wide band gap (~8.9 eV), high thermal stability with Si and Pt, high dielectric constant (~8) and large breakdown electric field [10,14,19,20,21,22] as Kim et al has reported [19,20,23,24,25,26]. In addition, the superior elasticity [27] and high toughness [28] make it possible for AlO x to be applied under various conditions including vibration and pressure environments [29,30,31]. Cano et al reported that AlO x -based dielectric layer showed superior stability under environments with hydrofluoric acid pressure [29] and Choi et al reported large-scale flexible electronics application with AlO x thin film [31], which have demonstrated that the AlO x thin film has great potential as a metal oxide layer in RRAM devices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the superior elasticity [27] and high toughness [28] make it possible for AlO x to be applied under various conditions including vibration and pressure environments [29,30,31]. Cano et al reported that AlO x -based dielectric layer showed superior stability under environments with hydrofluoric acid pressure [29] and Choi et al reported large-scale flexible electronics application with AlO x thin film [31], which have demonstrated that the AlO x thin film has great potential as a metal oxide layer in RRAM devices.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal ALE processes often include fluorination, chlorination, or oxidation reactions, which readily proceed at elevated substrate temperatures without the need for a plasma. 10,11,[14][15][16][17][18][19][20][21] As an emerging technique, the research on isotropic thermal ALE has focused on finding viable precursors and co-reactants to achieve etching of a variety of materials. A selection of these isotropic ALE processes can be seen in Table I.…”
mentioning
confidence: 99%
“…21,25 ALE of Al 2 O 3 has previously been achieved by using fluorinating reactants, such as hydrogen fluoride (HF) derived from HF pyridine or sulphur tetrafluoride (SF 4 ), combined with tri-methyl aluminium [TMA, Al(CH 3 ) 3 ], dimethyl aluminium chloride [DMAC, AlCl(CH 3 ) 2 ], or tin acetylacetone [Sn(acac) 2 ] as an etchant. [14][15][16][17][18][19][20] One of the most documented approaches for ALE of Al 2 O 3 is the use of HF and TMA. 10,[14][15][16][17][18][19] Half-cycle A of this thermal ALE process consists of the formation of an AlF 3 /AlO x F y surface layer by exposure to HF gas.…”
mentioning
confidence: 99%
See 1 more Smart Citation